RETRACTION: Benign Prostatic Hyperplasia Wound after Surgical Removal in Subjects on Anticoagulant or Antiplatelet Therapy: A Meta‐Analysis (International wound journal, 2025)
RETRACTION: X. Ji, Y. Zhao, L. Zhang, and Y. Liu, “Benign Prostatic Hyperplasia Wound after Surgical Removal in Subjects on Anticoagulant or Antiplatelet Therapy: A Meta‐Analysis,” International Wound Journal 19, no. 8 (2022): 1990–1999, https://doi.org/10.1111/iwj.13799. The above article, published online on 14 April 2022, in Wiley Online Library (http://onlinelibrary.wiley.com/), has been retracted by agreement between the journal Editor in Chief, Professor Keith Harding; and John Wiley & Sons Ltd. An Expression of Concern had previously been published to alert readers to concerns regarding data presented in Tables 1 and 2 [https://doi.org/10.1111/iwj.14303]. Following an investigation by the publisher, all parties have concluded that this article was accepted solely on the basis of a compromised peer review process. The editors have therefore decided to retract the article. The authors did not respond to our notice regarding the retraction.